Comparison of Rat Connective Tissue Response to BioMTA, Angelus MTA, and Root MTA - Marzieh Alimohammadi; Sina Mirzaee-Rad; Farideh Feizi; Hadi Shirzad Juybari; Akam Saeidi; Hemmat Gholinia (International Journal of Biomaterials)
Due to the widespread use of MTA in dentistry and various brands of this product, we decided to compare the three brands available in the country market by their biocompatibility. We divided 20 male Wistar rats into four groups. After local anesthesia and washing, we made two incisions on both sides (4 incisions in total). The experimental groups were Angelus MTA (Angelus, Brazil), BioMTA (CERKAMED, Poland), Root MTA (Dr. Lotfi, Tabriz, Iran), and the control group. The resulting paste was placed in a tube and implanted subcutaneously into male Wistar rats. Wistar rats were sacrificed 7, 15, 30, and 60 days later, with high anesthetic doses. The sample implanted in 10% formalin was stabilized after tissue processing and H&E staining under a microscope. The inflammatory reaction in the tissues received different scores at the beginning of the tube opening. BioMTA had the highest inflammatory response among the groups, but the difference was not statistically significant (p > 0.05). Also, there was no significant difference between the groups’ granulation and calcification (p < 0.05). There was a significant difference between BioMTA, Angelus MTA, Root MTA, and control groups in fibrous capsule formation (p < 0.05). Angelus MTA showed the lowest mean fibrous capsule formation in all periods. The effects of Angelus MTA, Root MTA, and BioMTA on connective tissue were investigated and compared. According to this study, these materials have good biocompatibility. According to the findings and statistical analysis, Angelus MTA has the most biocompatibility.